Balancing String Instruction in an Instrumental Lab Setting: An Intrinsic Evaluative Case Study. Issue 1 (July 2021) - Smith, Tawnya D.; Hendricks, Karin S.; Kos, Ronald P.; Goodrich, Andrew
There is an expected increase in the need to provide adequate string-specific training for non-string specialists in the future and for preservice music teachers to develop the requisite pedagogical content knowledge to teach a variety of instruments. A multiyear instrumental lab ensemble university course was designed to help preservice music teachers integrate knowledge and skills in various instrument- and ensemble-specific areas. The purpose of this intrinsic evaluative study was to determine the extent to which the new course was successful toward these aims. Data included interviews of students and instructors, observations of lab classes, and reflective journals of teaching faculty and two external observers. Data were coded and then analyzed using the program goal statements found in the course syllabus. Findings indicated that students considered the lab format more authentic to their teacher preparation than their previous coursework, and that performance and pedagogy skills on secondary instruments elevated more rapidly than anticipated. Recommendations include the need for more explicit connection between course readings and lab activities, and improved guidelines for course teaching assistants.